Advisor Interaction Goals and Verbal Messages: Merging a Multiple Goals Approach and the Integrated Model of Advice Giving. (June 2020) - Guntzviller, Lisa M.; Pulido, Manuel D.; Liao, Danni; Butkowski, Chelsea P.
Based on the integrated model of advice giving and theorizing about interaction goals, we examined how advisors' goal intensity and complexity predicted perceptions of advisor harmfulness and helpfulness. We also examined predictors of goal intensity and complexity, such as advisors' relational satisfaction with recipients, which generally increased goal intensity and complexity. Recipients and advisors rated advisors' behaviors as more helpful when advisors reported greater intensity of the problem-solving goal but not the other three goals (emotional support, eliciting disclosure, and facilitating reappraisal). However, recipients and advisors rated advisors' behaviors as more harmful when advisors had low versus moderate or high goal complexity. Qualitative analyses of conversation transcripts revealed patterns of interaction behavior associated with goal intensity and complexity. We discuss how goal intensity and complexity may relate to advisors' messages and interaction patterns during the conversation, and therefore recipient and advisor perceptions of advisors' helpfulness and harmfulness.